VPO1 Modulates Vascular Smooth Muscle Cell Phenotypic Switch by Activating Extracellular Signal‐regulated Kinase 1/2 (ERK 1/2) in Abdominal Aortic Aneurysms - Peng, Huihui; Zhang, Kai; Liu, Zhaoya; Xu, Qian; You, Baiyang; Li, Chan; Cao, Jing; Zhou, Honghua; Li, Xiaohui; Chen, Jia; Cheng, Guangjie; Shi, Ruizheng; et al. (Journal of the American Heart Association, 2018)
Background Hydrogen peroxide (H O ) is a critical molecular signal in the development of abdominal aortic aneurysm ( AAA ) formation. Vascular peroxidase 1 ( VPO 1) catalyzes the production of hypochlorous acid ( HOC l) from H O and significantly enhances oxidative stress. The switch from a contractile phenotype to a synthetic one in vascular smooth muscle cells ( VSMC s) is driven by reactive oxygen species and is recognized as an early and important event in AAA formation. This study aims to determine if VPO 1 plays a critical role in the development of AAA by regulating VSMC phenotypic switch. Methods and Results VPO 1 is upregulated in human and elastase-induced mouse aneurysmal tissues compared with healthy control tissues. Additionally, KLF 4, a nuclear transcriptional factor, is upregulated in aneurysmatic tissues along with a concomitant downregulation of differentiated smooth muscle cell markers and an increase of synthetic phenotypic markers, indicating VSMC phenotypic switch in these diseased tissues. In cultured VSMC s from rat abdominal aorta, H O treatment significantly increases VPO 1 expression and HOC l levels as well as VSMC phenotypic switch. In support of these findings, depletion of VPO 1 significantly attenuates the effects of H O and HOC l treatment. Furthermore, HOC l treatment promotes VSMC phenotypic switch and ERK 1/2 phosphorylation. Pretreatment with U0126 (a specific inhibitor of ERK 1/2) significantly attenuates HOC l-induced VSMC phenotypic switch. Conclusions Our results demonstrate that VPO 1 modulates VSMC phenotypic switch through the H O / VPO 1/ HOC l/ ERK 1/2 signaling pathway and plays a key role in the development of AAA . Our findings also implicate VPO 1 as a novel signaling node that mediates VSMC phenotypic switch and plays a key role in the development of AAA . Clinical Trial Registration URL : www.chictr.org.cn . Unique identifier: Chi CTR 1800016922.